Clinical Course of Different Types of Immune Reactions following Keratoplasty - Keye, Philip; Lapp, Thabo; Böhringer, Daniel; Heinzelmann, Sonja; Maier, Philip; Reinhard, Thomas (Klinische Monatsblätter für Augenheilkunde, 2021)
Background Immune-mediated corneal graft rejection (IR) is a leading cause of corneal graft failure. The endothelium, stroma, epithelium, or a combination can be affected. Little is known about the long-term outcomes of different types of IR.Methods We reviewed the medical records of all keratoplasties that had been performed at our eye centre between 2003 and 2016 (n = 3934) for any kind of IR that occurred between the surgery and 2019. All patients with a definite diagnosis of IR and sufficient clinical data were included in the analysis. IRs were grouped according to the affected part of the graft (endothelial, stromal, epithelial, and mixed). We analysed the dynamics of recovery and the clinical outcomes.Results We identified a total of 319 patients with IR. Twenty-seven of those were lost to follow-up and were excluded from further analysis. Of the IRs, 89% affected the endothelium. Endothelial IR resulted more frequently in a considerable loss of endothelial cell density than other forms of IR. Stromal IR showed a lower relapse rate and a better visual recovery than other types of IR and resulted less often in a failure of the graft.Conclusions We herein report comprehensive data about the prognosis regarding functional recovery after different types of IR following keratoplasty. Our data underline that timely recognition and correct classification of IR are important because they determine the clinical course and prognosis.
Keywords: corneal graft rejection; keratoplasty; clinical registry data